Impact of an empathy-based mental health first aid intervention using the SUFA model on anxiety and depression among adolescents: a quasi-experimental study - Sulastri Sulastri; Siti Fatonah; Yuniastini Yuniastini; Giri Udani; Allan Harris (International Journal of Public Health Science (IJPHS), 2026)
This study evaluated the effectiveness of an empathy-based mental health first aid (MHFA) intervention through structured SUFA mentoring by peer counselors in reducing symptoms of anxiety and depression in adolescents. The design used was a quasi-experimental, one-group pretest-posttest study conducted over two weeks in middle and high schools. A total of 100 students were trained as peer counselors, and each mentored one adolescent (a 1:1 ratio). Symptoms were measured before and after the intervention using the Mini MINDHEAR Youth Scale V.1. Analysis included descriptive statistics (mean pre–post scores and changes in symptom categories of "mild/none" vs. "moderate") and McNemar test (α = 0.05) to assess changes in categories. Respondents were predominantly female (67%), in late adolescence (58.18%), and high school students (55%). The mean anxiety score decreased from 4.92 to 3.50 (Δ = 1.42), while depression decreased from 5.05 to 3.21 (Δ = 1.84). The proportion of mild/none anxiety increased from 13 to 56, and moderate decreased from 87 to 44 (p = 0.003). A similar pattern occurred for depression: mild/none increased from 13 to 61, while moderate decreased (p = 0.001). SUFA-based peer counseling interventions significantly reduce symptoms of anxiety and depression in adolescents. Schools should integrate structured peer counselor training programs into mental health frameworks, establish systematic early detection protocols, and establish clear referral pathways to professional services within school-based support systems. The limitations of this study were no control group and short duration, which must be addressed in subsequent research.